Populasi Bakteri Antagonistik terhadap Fusarium sp. dari Rizosfer Lada Sehat dan Sakit Kuning - Suwandi Suwandi; Abdul Mazid; Surahman Surahman (Universitas Gadjah Mada, 2001)
Populations of antagonistic bacteria colonizing rhizosphere of diseased and healthy black pepper plants were compared to explore the biocontrol function of these populations on yellow disease of black pepper. As many as 180 isolates (equivalent to population of 1.8 x 1010 cfu/g fresh weight of root) were randomly selected and tested for their antagonistic activities against Fusarium sp., a pathogen of yellow disease. To characterize the populations, the isolates were tested for their fluorescent and Gram reaction. There was an evidence of significant association between antagonistic activities and the disease incidence. We found the significant larger proportion of antagonistic bacteria from the rhizosphere of healthy black pepper, whereas no significant difference between proportion of antagonistic and non-antagonistic population from yellow disease-affected rhizosphere. Populations of antagonistic bacteria were dominated by the population of non-fluorescent Gram-negative. Most of the fluorescent populations were antagonistic to Fusarium sp.